Penggunaan Merkuri pada Tambang Emas Ilegal: Diaturkah Dalam Minamata Convention? - Farisi, Mochammad; Putra, Akbar Kurnia; Novianti, Novianti (Uti Possidetis: Journal of International Law, 2022)
Exploration activities and exploitation of natural resources are examples of causes of damage by human activities. One of the activities that are rampant in Indonesia is mining activities, one of which is unlicensed gold mining (PETI). These activities can have a sustainable impact on environmental damage and pollution and bring a number of adverse impacts to various sectors such as environmental, social and health which in the process use toxic materials, namely mercury, so that waste from mining can pollute rivers and the surrounding nature. So to avoid this, the Minamata Convention on Mercury is present as an international agreement that aims to reduce and eliminate the impact of mercury on environmental and human health. To implement the Convention, the Government of Indonesia has ratified the convention by issuing Law of the Republic of Indonesia Number 11 of 2017 concerning Ratification of the Minamata Convention on Mercury and Presidential Regulation Number 21 of 2019 concerning the National Action Plan for Reducing Mercury Elimination (RAN-PPM). Following up on these rules, law enforcement must be carried out on the activities of PETI which in the process used mercury.